Posted by Jon on Monday, February 18, 2008 at 11:39am.
Your very first step is incorrect. Try this:
x + 3y = 0
x + 5/2 y = 1/2
Now subtract the last eq. from the first.
y/2 = -1/2
y = -1
your solution is "riddled" with errors
2x + 5y = 1 solved for y is y = (1-2x)/5
not y = 5 - 2x like you had.
Even if it had been right, x + 15 - 6x = 0
-5x = -15 , not 7x=15 like you had
lets start over.
Why not solve the second equation for x? (look for the "single" variable)
x = -3y sub that back into the first
2(-3y) + 5y = 1
-y = 1
y = -1 looks like your D was the right guess.
- 15 x ² + 2x + 13 = 0
Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...
Math - Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31...
Math - solve each system 1) 3x + y = 6 2x + 3y = 13 2) 2x + 5y - 6 = 0 -2x + y...
math - Solve the systems of equations by elimination. 1. -2x+y=7 2. 2x+y=-9 6x+...
ALGEBRA 1!PLZ HELP! - Use the Substitution method to solve the system of ...
math, beginning algebra - can someone correct this for me. Directions: Solve ...
Algebra 1 - I need help to this mathe problems... 1.Elimination using ...
Algebra2(check part 1) - 1)Solve the matrix:[2x] for x [3y]= answer=7 2)...
bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...
equations - solve the equation 3y square-XY=0 equation(1) 2X-5Y=1 eqn (2)
For Further Reading